Determinants of Chinese Stock Market Returns - Wang, Fei (2012)
This paper focuses on the macroeconomic variables underlying relationship with stock market returns for China stock market over the period 2000 to 2010. Chinese’s economy has experienced large change and it has also grown rapidly over the years. Chinese’s economy has experienced substantial growth and taken over Japan which used to be the second largest in terms of economy. Based on the specialty of China, this research focuses on Chinese stock market. Data were analyzed using SPSS, by gathering six variables that include inflation, oil price, gross domestic product, exchange rate change, net export and money supply. The study uses Arbitrage Pricing Theory as the basis for analysis. Correlation and regression result analyses were used to examine the relationship between macroeconomics variables and stock returns. The results indicate that five variables to have significant relationship with the dependent variable. Moreover, the results also indicate the level of influence that each macroeconomic variable has on the dependent variable. The findings are discussed and recommendations for future research are presented.